Analysis of Muscle Fatigue associated with Prolonged Standing Tasks in Manufacturing Industry - Isa , Halim (2010)
In most assembly lines in manufacturing industry and service occupations, employees may experience pain and discomfort associated with long periods of standing. Prolonged standing tasks in manufacturing industry may lead to musculoskeletal disorders including pain, increased fatigue and stiffness in active muscles. The aims of this study are to determine subjective fatigue experienced by male Malaysian operators in metal stamping industry, and assess muscle fatigue in their lower extremities. Ten production operators of the industry participated in the study. Muscle fatigue has been analyzed using surface electromyography(sEMG) whereby six muscles such as left and right erector spinae muscles, left and right tibialis anterior muscles, and left and right gastrocnemius muscles were simultaneously measured. On the other hand, the subjective fatigue was assessed through questionnaire surveys. Results of questionnaire surveys found that all operators involved in the study reported that they experienced muscle fatigue due to prolonged standing tasks. Result obtained from sEMG measurement shows similar trend with the conclusion derived from surveys. Workers who experienced fatigue recorded a decreased average mean.